Slip‐Dependence of Fault Frictional Stability Under Hydrothermal Conditions - Wei Feng; Lu Yao; Rodrigo Gomila; Shengli Ma; Giorgio Pennacchioni; Giulio Di Toro (Geophysical Research Letters)
Abstract In the rate‐state friction law framework, the transition from velocity weakening (V‐W) to velocity strengthening (V‐S) behavior marks the base of the seismogenic crust. Here we investigate the role of fault slip displacement under hydrothermal conditions in controlling the V‐W to V‐S transition. We shear simulated gabbro gouges at slip velocities ranging from 16 nm/s (∼50 cm/year) to 10 μm/s (∼8 cm/day) under hydrothermal conditions (300–400°C temperature; 30 MPa pore fluid pressure). We observe that cumulative fault slip increases the critical velocity for the V‐W to V‐S transition. The transition is accompanied by localized to distributed deformation mode, the formation of smectite‐type clays and occurrence of intergranular mass transfer. Our results provide insights into understanding the deepening and shallowing of V‐W/V‐S boundary (lower limit of the seismogenic zone) following a mainshock. Besides strain rate effects, slip‐enhanced chemical alteration and grain size‐sensitive deformation may temporarily contribute to the shallowing process.